The Effect of Differentiated Instruction based on Multiple Intelligences toward Critical Thinking and Student Self-Efficacy - Khairul Bariyah; Sugiman Sugiman (Didaktik Matematika, 2024)
Mathematics learning is often teacher-centered, where teachers directly present material to students without considering students' learning needs and improving their critical thinking skills. The lack of students' self-efficacy as a motivational factor will affect the development of their critical thinking level.This studyaims to determine the effectiveness of differentiatedinstructionbased on multiple intelligences to improve student's critical thinking and self-efficacy.This research employed a quantitative approach and a quasi-experimental research design. This study focused on mathematics learning using the differentiated instruction approach in the vector topic for Year 10 students in one senior high school at Langsa, Aceh, Indonesiaand compared differentiated instruction and scientific approach. Based on the population, the experimental group implemented differentiated instruction, and the control group applied a scientific approach. The hypothesis was tested using MANOVA, Hotelling's T2test, and independent sample t-test. The effect size of differentiated instruction was determined based on the Cohen d-effect size calculation. The results of this study indicate that differentiated instruction has a moderate effect on students' critical thinking but does not significantly affect their self-efficacy. Therefore, differentiated instruction can be considered as one of the effective approaches for enhancing students' critical thinking skills.